Piling, European practice and worldwide trends proceedings of a conference organized by the Institution of Civil Engineers, and held in London on 7-9 April 1992 - Sands, M. J. (T. Telford, 1992)
Authors from throughout Europe have contributed to this book, which covers the design advances in piling practice, performance testing and innovations in piling systems, piling systems employed in different European countries, trends and technologies and research and developments, taking into account geographical and soil conditions as they determine the state of the art.